2014
DOI: 10.3109/07420528.2013.872121
|View full text |Cite
|
Sign up to set email alerts
|

Does one hour of bright or short-wavelength filtered tablet screenlight have a meaningful effect on adolescents’ pre-bedtime alertness, sleep, and daytime functioning?

Abstract: Electronic media use is prevalent among adolescent populations, as is the frequency of sleeplessness. One mechanism proposed for technology affecting adolescents' sleep is the alerting effects from bright screens. Two explanations are provided. First, screens emit significant amounts of short-wavelength light (i.e. blue), which produces acute alertness and alters sleep timing. Second, later chronotypes are hypothesised to be hypersensitive to evening light. This study analysed the pre-sleep alertness (GO/NOGO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 59 publications
2
80
1
Order By: Relevance
“…Of particular interest in this young student population is the impact of light-emitting devices on sleep and the circadian clock. Although such devices have been found to impact sleep and circadian timing (Cajochen et al 2011; Chang et al 2015), the findings are mixed (Heath et al 2014; Rangtell et al 2016) and these changes are often small; thus, the real-world significance of these findings remains unclear (Zeitzer 2015). The findings from this study, however, emphasise that environmental evening light exposure may need to be tailored for different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this young student population is the impact of light-emitting devices on sleep and the circadian clock. Although such devices have been found to impact sleep and circadian timing (Cajochen et al 2011; Chang et al 2015), the findings are mixed (Heath et al 2014; Rangtell et al 2016) and these changes are often small; thus, the real-world significance of these findings remains unclear (Zeitzer 2015). The findings from this study, however, emphasise that environmental evening light exposure may need to be tailored for different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Typical TV content caused one-third of the irradiance compared to PC use. Heath et al (2014) found that 1 h of tablet use prior to bedtime did not significantly impact circadian phase. While used at a close distance, smartphones and tablets are not large enough to reach the 50-lx threshold.…”
Section: Screen Use Activitiesmentioning
confidence: 97%
“…Previous study protocols administered continuous screen use for 1-5 h (Cajochen et al, 2011;Heath et al, 2014;Chang et al, 2015;van der Lely et al, 2015) when investigating circadian phase shifts due to screen use. Wood et al (2013) found measurable melatonin suppression after 2 h of tablet use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations